The Role of the Village Government in the Relocation of Bong Suwung Localization, Yogyakarta City - Pamungkas Pamungkas; Sugiyanto Sugiyanto (International Journal of Law and Society, 2025)
The Special Region of Yogyakarta (DIY) is known as an important tourist destination, and tourism development requires an increase in both demand and supply sides. Transportation, especially Tugu Yogyakarta Station managed by PT Kereta Api Indonesia (KAI), is an important element in the offer aspect. PT KAI seeks to improve the quality of service by relocating residents from the Bong Suwung area in Gedongtengen District to facilitate the arrangement of the area around the station. This process involves the socialization and execution stages to reduce conflicts with residents. Yogyakarta Mayor Regulation Number 121 of 2020 regulates the role of urban villages in providing protection for the community. This study uses a qualitative approach focusing on policy research with. The research location is in Bong Suwung, Pringgokusuman Village, Gedongtengen Village, Yogyakarta City. Data is collected by observation, interview, and documentation techniques, primary and secondary data are integrated in the context of analysis, informance is determined by propursive sampling. The results of the study show that even though the Village has carried out data collection, socialization, and coordination with related parties, the aspect of economic empowerment for ex-prostitutes is still very minimal. The reluctance of the Village to be more involved in the training and economic empowerment program, on the grounds that the program is not part of the activities of the Yogyakarta City Government, creates a gap in coordination between institutions and hinders the socio-economic recovery of the affected communities.